Critical review of the evidence for Vojta Therapy: a systematic review and meta-analysis - Sánchez-González, Juan Luis; Sanz-Esteban, Ismael; Menéndez-Pardiñas, Mónica; Navarro-López, Víctor; Sanz-Mengíbar, José Manuel (Frontiers in Neurology, 2024)
Introduction It is essential to link the theoretical framework of any neurophysiotherapy approach with a detailed analysis of the central motor control mechanisms that influence motor behavior. Vojta therapy (VT) falls within interventions aiming to modify neuronal activity. Although it is often mistakenly perceived as exclusively pediatric, its utility spans various functional disorders by acting on central pattern modulation. This study aims to review the existing evidence on the effectiveness of VT across a wide range of conditions, both in the adult population and in pediatrics, and analyze common therapeutic mechanisms, focusing on motor control modulation. Aim The goals of this systematic review are to delineate the existing body of evidence concerning the efficacy of Vojta therapy (VT) in treating a broad range of conditions, as well as understand the common therapeutic mechanisms underlying VT with a specific focus on the neuromodulation of motor control parameters. Methods PubMed, Cochrane Library, SCOPUS, Web of Science, and Embase databases were searched for eligible studies. The methodological quality of the studies was assessed using the PEDro list and the Risk-Of-Bias Tool to assess the risk of bias in randomized trials. Methodological quality was evaluated using the Risk-Of-Bias Tool for randomized trials. Random-effects meta-analyses with 95% CI were used to quantify the change scores between the VT and control groups. The certainty of our findings (the closeness of the estimated effect to the true effect) was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). Results Fifty-five studies were included in the qualitative analysis and 18 in the meta-analysis. Significant differences in cortical activity (p = 0.0001) and muscle activity (p = 0.001) were observed in adults undergoing VT compared to the control, as well as in balance in those living with multiple sclerosis (p < 0.03). Non-significant differences were found in the meta-analysis when evaluating gross motor function, oxygen saturation, respiratory rate, height, and head circumference in pediatrics. Conclusion Although current evidence supporting VT is limited in quality, there are indications suggesting its potential usefulness for the treatment of respiratory, neurological, and orthopedic pathology. This systematic review and meta-analysis show the robustness of the neurophysiological mechanisms of VT, and that it could be an effective tool for the treatment of balance in adult neurological pathology. Neuromodulation of motor control areas has been confirmed by research focusing on the neurophysiological mechanisms underlying the therapeutic efficacy of VT. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=476848, CRD42023476848.